Butterfly Hug Therapy: Pelatihan Bagi Ibu dengan Inner Child Negatif - Harahap, Ade Chita Putri; Harahap, Dinda Permatasari; Simarmata, Sari Wardani; Armitasari , Armitasari (Universitas Nahdlatul Ulama Sumatera Utara, 2025)
Mental health is a crucial aspect of an individual's overall well-being. Untreated mental health conditions, particularly unresolved past trauma or issues related to the